MicroRNA-199a-3p regulates proliferation and milk fat synthesis of ovine mammary epithelial cells by targeting VLDLR - Wang, Jiqing; Hao, Zhiyun; Hu, Liyan; Qiao, Lirong; Luo, Yuzhu; Hu, Jiang; Liu, Xiu; Li, Shaobin; Zhao, Fangfang; Shen, Jiyuan; Li, Mingna; Zhao, Zhidong (Frontiers in Veterinary Science, 2022)
The microRNAs (miRNAs) have been shown to play essential roles in mammary epithelial cells (MECs) activities and mammary gland development. However, there have been no reports describing the function of miR-199a-3p in MECs and the biological mechanisms by which the miRNA affects cell proliferation and milk fat synthesis in mammals. In the study, the effect of miR-199a-3p on viability, proliferation, and milk fat synthesis of ovine mammary epithelial cells (OMECs) was investigated, and the target relationship of the miRNA with very low-density lipoprotein receptor gene (VLDLR) was also verified. Transfection with a miR-199a-3p mimic increased the viability of OMECs and the number of Edu-labeled positive OMECs. In contrast, a miR-199-3p inhibitor had the opposite effect with the miR-199a-3p mimic. The expression levels of three marker genes were also regulated by both the miR-199a-3p mimic and miR-199-3p inhibitor in OMECs. Together these results suggest that miR-199a-3p promotes the viability and proliferation of OMECs. A dual luciferase assay confirmed that miR-199a-3p can target VLDLR by binding to the 3'-untranslated regions (3'UTR) of the gene. Further studies found a negative correlation in expression of miR-199a-3p with VLDLR. The miR-199a-3p mimic decreased the content of triglycerides, as well as the expression levels of six milk fat synthesis marker genes in OMECs, including lipoprotein lipase gene (LPL), acetyl-CoA carboxylase alpha gene (ACACA), fatty acid binding protein 3 gene (FABP3), CD36, stearoyl-CoA desaturase gene (SCD) and fatty acid synthase gene (FASN). The inhibition of miR-199a-3p increased the level of triglycerides and the expression of LPL, ACACA, FABP3, SCD and FASN in OMECs. These findings suggest that miR-199a-3p inhibited milk fat synthesis of OMECs. This is the first study to reveal the molecular mechanisms by which miR-199a-3p regulates proliferation and milk fat synthesis of OMECs in sheep.